2023
DOI: 10.1186/s13045-023-01423-7
|View full text |Cite
|
Sign up to set email alerts
|

Passive pre-exposure immunization by tixagevimab/cilgavimab in patients with hematological malignancy and COVID-19: matched-paired analysis in the EPICOVIDEHA registry

Abstract: Only few studies have analyzed the efficacy of tixagevimab/cilgavimab to prevent severe Coronavirus disease 2019 (COVID-19) and related complications in hematologic malignancies (HM) patients. Here, we report cases of breakthrough COVID-19 after prophylactic tixagevimab/cilgavimab from the EPICOVIDEHA registry). We identified 47 patients that had received prophylaxis with tixagevimab/cilgavimab in the EPICOVIDEHA registry. Lymphoproliferative disorders (44/47, 93.6%) were the main underlying HM. SARS-CoV-2 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
13
1
1
Order By: Relevance
“…In the EPICOVIDEHA registry, a matched-control cases analysis was performed, showing a 90% breakthrough infection rate, higher than in our study, with a comparable death rate, but with the limit of a small cohort (n=47) (Table 2). 12 In the present experience, no risk factors associated with severe COVID-19 or hospitalization, or death were identified, in contrast with our previous experience, which focused on the treatment of COVID-19 with MoAbs other than T-C, where the presence of comorbidity was associated with the risk of developing COVID-19 infection, and hospitalization and oxygen requirement were confirmed as prognostic factors for COVID-19 related death. 5 Similarly, as recently reported by Laracy et al in a large cohort of patients (n=892) including different hematological malignancies, there were no risk factors that allowed to foresee the infectious outcome in this setting except for the augmented schedule of T-C MoAb (Table 2).…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…In the EPICOVIDEHA registry, a matched-control cases analysis was performed, showing a 90% breakthrough infection rate, higher than in our study, with a comparable death rate, but with the limit of a small cohort (n=47) (Table 2). 12 In the present experience, no risk factors associated with severe COVID-19 or hospitalization, or death were identified, in contrast with our previous experience, which focused on the treatment of COVID-19 with MoAbs other than T-C, where the presence of comorbidity was associated with the risk of developing COVID-19 infection, and hospitalization and oxygen requirement were confirmed as prognostic factors for COVID-19 related death. 5 Similarly, as recently reported by Laracy et al in a large cohort of patients (n=892) including different hematological malignancies, there were no risk factors that allowed to foresee the infectious outcome in this setting except for the augmented schedule of T-C MoAb (Table 2).…”
contrasting
confidence: 96%
“…9 However, recent studies, mainly performed in vitro, suggested inferior efficacy against omicron variants. [10][11][12] Our aim was to evaluate if this strategy's upcoming reported clinical benefit and safety to patients with hematologic malignancies were still in force in a reallife setting of high-risk hematologic patients during the omicron-predominant COVID-19 wave in Italy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] On the other hand, studies would suggest that severity of disease and mortality rates are ameliorated also in this category of patients, mainly thanks to appropriate vaccination policies. 2,27 Furthermore, some preliminary, encouraging data, has been reported about preexposure prophylaxis with monoclonal antibodies against SARS-CoV-2 [28][29][30] and early start after SARS-CoV-2 infection with antiviral drugs 31,32 to prevent the progression to critical disease in severely immuno-compromised populations, such as MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Only a few series to date have evaluated the efficacy of tixagevimab-cilgavimab as primary prophylaxis in patients with various HMTs, with conflicting results. [3][4][5] This cohort study aimed to compare the incidence and severity of COVID-19 among adult patients affected by HMTs who prophylactically received tixagevimab-cilgavimab and those who did not. From June 2022 to March 2023, Omicron variants were prevalent in Italy.…”
mentioning
confidence: 99%